The Influence of Compensation, Non-Physical Work Environment, Workload, and Motivation on Employee Performance - Talakua, Christi Natalia; Latupapua, Conchita V.; Pentury, Gerrit M. (SEAN Institute, 2024)
Compensation is an institution's obligation to provide justice to its employees in accordance with the amount of workload and performance achieved. This research aims to analyze and explain: the effect of compensation on partner performance. the influence of the non-physical work environment on employee performance. The effect of workload on employee performance. The influence of work motivation on employee performance. This research was conducted by the Ambon City Central Statistics Agency (BPS). The sample in this research is a BPS partner with a research method using multiple linear regression, data processing using SPSS Vs 23 software. The research results prove that 1. compensation has a significant positive effect on employee performance. 2. The non-physical work environment has a significant positive effect on employee performance. 3. Workload has a significant negative effect on employee performance. 4. Work motivation has a significant positive effect on employee performance. Suggestions for future researchers: they can study this concept by adding the Organizational Culture variable, or further expanding the research object and using other data analysis methods.